2005
DOI: 10.1111/j.1365-2583.2004.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and transcriptional activation of lysozyme‐encoding cDNAs in the mosquito Aedes aegypti

Abstract: Lysozymes are enzymes characterized by their ability to break down bacterial cell walls. In insects certain lysozymes are only found in the midgut, whereas others are only found in the haemolymph and fat body after immune challenge. We identified two lysozyme-encoding cDNAs from Aedes aegypti. Both deduced protein sequences are basic in nature, contain 148 amino acids including eight highly conserved cysteine residues, and their genomic sequences contain a single intron. Transcriptional profiles indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Lysozymes, present in many organisms, cleave the β-1, 4-glycosidic linkage between N-acetylmuramic acid and N-acetylglucosamine found in certain bacterial cell walls [42]. Their functions have been widely described in species that ingest or harbour bacteria throughout their life cycles, such as M. domestica and D. melanogaster , and also characterized as digestive enzymes [42][45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysozymes, present in many organisms, cleave the β-1, 4-glycosidic linkage between N-acetylmuramic acid and N-acetylglucosamine found in certain bacterial cell walls [42]. Their functions have been widely described in species that ingest or harbour bacteria throughout their life cycles, such as M. domestica and D. melanogaster , and also characterized as digestive enzymes [42][45].…”
Section: Resultsmentioning
confidence: 99%
“…Their functions have been widely described in species that ingest or harbour bacteria throughout their life cycles, such as M. domestica and D. melanogaster , and also characterized as digestive enzymes [42][45]. Other reports have suggested a major role of lysozymes in immune responses to pathogens [42], [46]. We found that two of the four lysozyme unigenes up-regulated and two other down-regulated post-infection, suggesting Musca lysozymes may function as defense molecules as well as digestive enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown an increased lysozyme expression in the mosquitoes after challenge with bacteria (Fujimoto et al, 2001; Lee and Brey, 1995; Sun et al, 1991; Gao and Fallon, 2000; Hernandez et al, 2003; Bedoya et al, 2005; Kajla et al, 2010). In blood fed mosquitoes the bacterial population increases significantly within the midgut (Beier, 1998, DeMaio et al, 1996; Pumpuni et al, 1993, 1996; Bedoya et al, 2005). Recently Dong et al (2009) showed that the presence of gut microbiota indirectly impacted the susceptibility of the mosquitoes to become infected with malaria parasites apparently via modulation of the basal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Because mosquito lysozymes belong to an expanded gene family (Li et al, 2005; Bedoya et al, 2005), we are also interested in investigating the biological functions of each member of the group. As a first step towards that goal, we analyzed the expression profiles for AdLys c-1 across stages and tissues of An.…”
Section: Discussionmentioning
confidence: 99%
“…C- and i-type lysozymes have been reported in several insect orders, including Diptera, Lepidoptera, Orthoptera, Isoptera, and Hemiptera 12-14. For example, thirteen, eight, and six c-type lysozyme genes are identified in the genome of Drosophila melanogaster 15, Anopheles gambiae 16, and Aedes agypti 17, respectively. Five of eighteen lysozyme genes in D. melanogaster encode i-type lysozymes 15.…”
Section: Introductionmentioning
confidence: 99%